2005
DOI: 10.1196/annals.1340.016
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Tractography of the Motor White Matter Tracts in Man: Current Controversies and Future Directions

Abstract: The anatomy of the brain is extremely complex, and certain, even large structures, such as the corticospinal tract (CST), remain poorly understood. Diffusion tractography provides an opportunity to explore the white matter tracts in a fundamentally new way. In the current paper, we show how this technique has already added to our understanding of the anatomy of the CST. We also explore the future projects involving diffusion tractography of the motor white matter tracts that will advance this method and furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 17 publications
2
59
1
2
Order By: Relevance
“…[37][38][39] The cingulum, which was reduced in preterm male subjects compared with control subjects, is involved in visual-spatial attention, sensorimotor function, and executive control according to both human and animal models. [40][41][42] Well-established primary motor and sensorimotor pathways including precentral gyrus, corticospinal and corticopontine tracts, superior thalamic radiation, middle cerebellar peduncle, basal ganglia, internal capsule, and corona radiata [43][44][45] also were significantly reduced in our sample of preterm male subjects. Boys born prematurely are known to be more likely to have moderate to severe cerebral palsy compared with girls, 46 and male sex has been related to poor general neuromotor behavior outcome at age 7 years.…”
Section: Discussionmentioning
confidence: 80%
“…[37][38][39] The cingulum, which was reduced in preterm male subjects compared with control subjects, is involved in visual-spatial attention, sensorimotor function, and executive control according to both human and animal models. [40][41][42] Well-established primary motor and sensorimotor pathways including precentral gyrus, corticospinal and corticopontine tracts, superior thalamic radiation, middle cerebellar peduncle, basal ganglia, internal capsule, and corona radiata [43][44][45] also were significantly reduced in our sample of preterm male subjects. Boys born prematurely are known to be more likely to have moderate to severe cerebral palsy compared with girls, 46 and male sex has been related to poor general neuromotor behavior outcome at age 7 years.…”
Section: Discussionmentioning
confidence: 80%
“…For example, symmetrical white matter injury close to the ventricle (leg fibers of the pyramidal systems are closest to the ventricles) is likely to be associated with diparesis, and involvement of broader areas of white matter, including areas further from the ventricle subserving arms, is likely to be associated with quadriparesis ( [62], [63], [64]). As a result, children with diparesis have brain lesions that are less likely to be located in white matter association areas that may impair cognition and they have lower rates of microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that fiber tracking of the motor tracts is inadequate in the lateral portions of the corticobulbar/spinal tract, 34,35 such as the mouth and tongue fiber tracts, and that these tracts can, therefore, not be successfully mapped by DT tractography. Holodny et al 36 reported that the corticobulbar tract (CBT) is probably too small to trace because when fibers cross, the fiber tracking algorithm will preferentially track the larger tract (ie, the CST or the longitudinal fasciculus). However, Thomas et al 37 successfully tracked the CBT in 5 patients with hemiparetic cerebral palsy in both hemispheres, by placing regions of interest in the internal capsule and in the cerebral peduncle and pons and by optimizing the angular deflection threshold.…”
Section: Figmentioning
confidence: 99%